Analisis Prestasi Mahasiswa Hafidz dan Hafidzah di Fakultas Kedokteran Universitas Muslim Indonesia - Zulfi Zain Alfaruq; Rachmat Faisal Syamsu; Nasrudin Andi Mappaware; Ida Royani; Armanto Makmun (Lembaga Yasin AlSys, 2026)
Although memorizing the Qur’an (tahfidz) is believed to contribute to cognitive abilities, emotion regulation, and spiritual intelligence, which are theoretically related to academic achievement, empirical evidence directly examining the relationship between tahfidz and academic performance among medical students remains mixed. This study aimed to analyze the relationship between the amount of memorization and the intensity of muraja’ah and the Cumulative Grade Point Average (CGPA) of hafidz and hafidzah students at the Faculty of Medicine, Universitas Muslim Indonesia. A quantitative descriptive–analytic approach with a cross-sectional design was employed, involving 81 hafidz/hafidzah students from the 2021–2023 cohorts selected using a total sampling technique. Data were collected through structured questionnaires and official academic records, then analyzed using the Kruskal–Wallis test due to the non-normal distribution of the data. The results showed that the majority of respondents had a high CGPA (≥ 3.50), but there was no significant relationship between the amount of memorization and CGPA (p = 0.616) nor between the intensity of muraja’ah and CGPA (p = 0.083). These findings indicate that the academic achievement of hafidz/hafidzah medical students is not solely determined by the quantity of memorization and the frequency of muraja’ah, but is also influenced by other factors such as self-regulation, learning motivation, and time management. This study enriches the discourse on spirituality and academic achievement in medical education and recommends further research using qualitative and longitudinal approaches to explore the psychosocial mechanisms underlying this relationship.